Adherencia al Tratamiento del Trastorno por Déficit de Atención e Hiperactividad (TDAH) en el Programa ChAMP UT-Health Houston. - Jadala, Rachitha P.; Temkin, Hali; Daniel, Kerri L.; Soutullo, Cesar A. (Medicina (Buenos Aires))
Introduction: ADHD has a safe and effective treat ment, but treatment adherence is often low. Several factors contribute to this low adherence, some of which are modifiable. Methods: We conducted a literature review of recent studies on medication adherence in children and adoles cents with ADHD. We gathered data on ADHD treatment adherence from our clinic in the ADHD Program and the Child and Adolescent Mood Disorders Program (ChAMP) at the University of Texas Health-Houston Program. We analyzed factors related to medication adherence, such as patient age, sex, prescription type, release formula, and their association with adherence in 117 patients with ADHD who were prescribed stimulant or non-stimulant medications. Results: We found publications identifying factors influencing medication adherence, including disorder characteristics, the patient, the healthcare system, socio-economic factors, the medication itself, and the envi ronment. Factors that can improve adherence include knowledge about ADHD, the medication, its benefits, and potential side effects; simple, once-daily extended-release medication regimens; patients younger than 12 years old; female sex; reduced barriers to accessing healthcare; and a positive, proactive attitude of parents toward ADHD and medication use. Discussion: Optimizing adherence and long-term prognosis of ADHD is achieved by reinforcing factors that increase adherence and reducing biases and lack of knowledge about ADHD.